School Heads’ Post Observation Practices in Tanzania: Feedback Implications for Teachers - Linus Chaula; Godlove Lawrent; Iramba Freddie Warioba Iramba (International Journal of Educational Administration, Management, and Leadership, 2022)
Clinical supervision is one of the best supervisory models that is user - friendly to school heads in supervising teachers’ professional practices. This paper examined teachers’ perception of school heads’ teaching and learning post - observation practices in improving teaching professional relations in public secondary schools in Tanzania. A mixed-methods and case research was conducted in Njombe Region, Tanzania. The study employed 122 respondents, whereby, 94 filled in the questionnaires and 28 participated in the semi - structured interviews and FGDs. The SPSS version 25 aided the analysis of quantitative data and qualitative data on the other hand were analysed through content analysis. The results show that 57.4% (n=70) of participants were male, of which 95.7% (n = 67) were teachers and 4.3% (n = 3) school heads. There were 42.6% (n = 52) of participants were female, of which 98.0% (n = 51) teachers and 2.0% (n = 1) school heads. There were 86.1% (n = 105) of participants with ages ranging from 25 and 50 years. Teachers positively perceived school heads’ post - observation practices (p < 0.05). However, unlike students, no statistical significant difference was observed in teachers’ working experiences regarding teachers' teaching profession relationships among themselves and school heads. It is concluded that school heads’ post - observation practices improve teachers’ professional relationships and could be practiced in supervising teachers in Tanzanian public secondary schools. Post - observation practices of school heads impart professional relationship skills to teachers. Teachers with professional relationship skills motivate students to participatory teaching and learning practice that contribute for an academic achievement.